Green algae Caulerpa racemosa compounds as antiviral candidates for SARS-CoV-2: In silico study - Tassakka, Asmi CMAR.; Iskandar, Israini W.; Juniyazaki, Andi BA.; Zaenab, St; Alam, Jamaluddin F.; Rasyid, Haerani; Kasmiati, Kasmiati; Sinurat, Ellya; Dwiany, Fenny M.; Martien, Ronni; Moore, Abigail M. (Narra Sains Indonesia, 2023)
Green algae (Caulerpa racemosa) are known to contain bioactive compounds which are hypothesized to have antiviral activities against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease 2019 (COVID-19) pandemic. The aim of this study was to analyze the anti-SARS-CoV-2 potential of compounds extracted from the green alga Caulerpa racemosa using in silico analysis. The extract was obtained through maceration with 96% ethanol and the compounds present in the extract were identified through gas chromatography-mass spectroscopy (GC-MS). The binding affinities were analyzed in silico using the PyRx application and visualized in the PyMOL software. GC-MS analysis of Caulerpa racemosa extract showed 92 spectral peaks, each of which was assigned to a bioactive compound. Of the six compounds with a strong binding affinity, n-[1-(1-adamantan-1-yl-propyl)-2,5-dioxo-4-trifluoromethyl-imidazo lidin-4-yl] 4-methoxy-benzamide had the lowest score (-8.1 kcal/mol) against the SARS-CoV-2 3C-like protease binding site, similar with that of remdesivir. The molecular dynamics calculations demonstrated that root means square deviation values of the selected inhibitors remained stable throughout a 15-nanosecond simulation. In conclusion, the in silico analysis suggests that Caulerpa racemosa extract is a potential antiviral candidate against SARS-CoV-2.